The CIPP Model of Stunting Management Program During Covid-19 Pandemic in Semarang City - Firmansyah Kholiq Pradana PH; Ayun Sriatmi; Apoina Kartini (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2022)
Background: Semarang City has successfully reduced in reducing the stunting rate by 2.7% in 2018 and 2.5% in 2019. With the Covid-19 pandemic, the stunting prevention program in Semarang City faces problems that have the potential to increase the prevalence risk of stunting. The problem are limited access of intervention and decline of the stunting program quality in work area of the Puskesmas in Semarang City. In addition, it is still unknown how the stunting program was implemented at the puskesmas during the Covid-19 pandemic.Objectives: The purpose of this research was to identify and evaluate the implementation of the stunting prevention program in Semarang City during the Covid-19 pandemic by using the CIPP model.Materials and Methods: This research used a survey research with a qualitative approach. This research was carried out from August to October 2021. The informants for this study consisted of 5 main informants: nutritionists at the puskesmas, 15 triangulation informants, the head of the puskesmas, posyandu cadres, and mothers who had stunted children in five health centers in Semarang City, namely Bandarharjo Health Center, Lamper Tengah Health Center, Tlogosari Wetan Health Center, Gunungpati Health Center, and Pegandan Health Center. Determination of informants using a purposive technique based on the geographic location of the Public Health Center. In-depth interviews used prepared guidelines. Data analysis used content analysis.Results: The results showed that the in the context component, the nutritionists had understood goals and targets of the stunting program. The input component showed that Human Resources was not optimal because they helped in succeed in the Covid-19 program. Funding was disrupted because there were still no technical guidelines for funding during the Covid, infrastructures were not optimal due to a lack of training for posyandu cadres. The process components included: a monitoring program that was carried out door to door, no administration of PMT F100, ineffective online counseling, fewer mothers who were participated in nutrition consultations, no monitoring related to vitamin A administration.Conclusion: The stunting prevention program in the work area of the puskesmas during the Covid-19 pandemic has not been able to be implemented well during the Covid-19 pandemic.